2022
DOI: 10.32859/era.24.23.1-21
|View full text |Cite
|
Sign up to set email alerts
|

Local ecological knowledge dynamics of farmers in areas which have been chronically disturbed by human actions in the Brazilian Caatinga

Abstract: Background: The diversity of plants indicated for the same use, plays important strategies which can affect the resilience of local ecological knowledge. In this context, we investigated the variation of local ecological knowledge through the richness of cited species, redundancy on an individual level and utilitarian redundancy (fuel, construction and technology) by local populations inserted in a dry forest with different environmental characteristics in northeastern Brazil.Methods: We conducted semi-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
5

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
2
4
0
5
Order By: Relevance
“…As predicted by the utilitarian redundancy model, redundancy contributes to the resilience of a species use system, as the more resources available for a given function, the greater the probability that each function will be met (Albuquerque & Oliveira, 2007; Medeiros et al, 2020; Nascimento et al, 2015). As a basis for comparison, there are some studies that analysed the redundancy of medicinal and timber knowledge systems and found results very similar to ours, both in the number of species for each function (Díaz‐Reviriego et al, 2016; Santoro et al, 2015) and in the Uredit value of medicinal (Medeiros et al, 2020) and firewood plants (Pedraza et al, 2022). Despite the relative scarcity of natural resources characteristic of the vegetation and climate of the Patagonian steppe, based on the URM, we can say that redundancy as an indicator of resilience processes in plant knowledge systems analysed in our study is similar to those found in other socio‐ecological systems, such as those of the Brazilian semiarid region (Medeiros et al, 2020; Pedrosa et al, 2022) and the Bolivian Amazon (Díaz‐Reviriego et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As predicted by the utilitarian redundancy model, redundancy contributes to the resilience of a species use system, as the more resources available for a given function, the greater the probability that each function will be met (Albuquerque & Oliveira, 2007; Medeiros et al, 2020; Nascimento et al, 2015). As a basis for comparison, there are some studies that analysed the redundancy of medicinal and timber knowledge systems and found results very similar to ours, both in the number of species for each function (Díaz‐Reviriego et al, 2016; Santoro et al, 2015) and in the Uredit value of medicinal (Medeiros et al, 2020) and firewood plants (Pedraza et al, 2022). Despite the relative scarcity of natural resources characteristic of the vegetation and climate of the Patagonian steppe, based on the URM, we can say that redundancy as an indicator of resilience processes in plant knowledge systems analysed in our study is similar to those found in other socio‐ecological systems, such as those of the Brazilian semiarid region (Medeiros et al, 2020; Pedrosa et al, 2022) and the Bolivian Amazon (Díaz‐Reviriego et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
“…Medeiros et al (2020) based on the redundancy analysis of medicinal plants to propose the utilitarian redundancy index, then they called as utilitarian redundancy index for the therapeutic indication (Uredit). However, it can be used for other usage categories (Pedraza et al, 2022). Uredit considers the number of species for each utilitarian function and the level of sharing that information about usage.…”
Section: Methodsmentioning
confidence: 99%
“…Como predice el modelo de redundancia utilitaria, la redundancia contribuye a la resiliencia de un sistema de uso de especies, ya que cuantos más recursos estén disponibles para una determinada función, mayor será la probabilidad de que cada función se cumpla (Albuquerque & Oliveira, 2007; Medeiros et al, 2020; Nascimento et al, 2015). Como base de comparación, existen algunos estudios que analizaron la redundancia de los sistemas de conocimiento de plantas medicinales y maderables y encontraron resultados muy similares a los nuestros, tanto en el número de especies para cada función (Díaz‐Reviriego et al, 2016; Santoro et al, 2015) como en el valour Uredit de las plantas medicinales (Medeiros et al, 2020) y para leña (Pedrosa et al, 2022). A pesar de la relativa escasez de recursos naturales característicos de la vegetación y el clima de la estepa patagónica, en base al MRU, podemos decir que la redundancia como indicador de procesos de resiliencia en los sistemas de conocimiento de plantas analizados en nuestro estudio es similar a la encontrada en otros sistemas socioecológicos, como los de la región semiárida brasileña (Medeiros et al, 2020; Pedrosa et al, 2022) y la Amazonía boliviana (Díaz‐Reviriego et al, 2016).…”
Section: Discussionunclassified
“…Como explicamos anteriormente, separamos la categoría medicinal en cada una de las subcategorías debido a la complejidad de la función medicinal. Otro trabajo que utilizó el Uredit para el uso de la madera (Pedrosa et al, 2022) hizo lo mismo con ese uso (separándolo en leña, construcción y tecnología). En nuestro estudio, no analizamos la complejidad del uso de la madera, ya que las comunidades la utilizaban principalmente para leña.…”
Section: Redundancia Utilitariaunclassified
See 1 more Smart Citation